Prevalence of obesity among urban and rural school going adolescents of Vadodara, India: a comparative study - Pathak, Sunil; Modi, Prashant; Labana, Urmil; Khimyani, Priya; Joshi, Amruta; Jadeja, Riddhi; Pandya, Meghavi (International Journal of Contemporary Pediatrics, 2018)
Background: Obesity is a major global problem among children. India has paradox of having both undernutrition and obesity as a major problem. This epidemic of obesity is also affecting rural population. It has both short and long term adverse health outcome. Methods: The present study is a cross-sectional, observational and questionnaire-based study conducted in urban and rural school going adolescents. Results: 188 subjects (89 rural and 99 urban school) school were enrolled. 17.6%(33), 20.2%(38), 59%(111) and 3.2%(6) children were obese, overweight, normal and underweight respectively. 65.22% of urban males & 62.26% females were either obese or overweight as compared to 15.78% of rural males and 3.92% females (p<0.0001). OR was 17.7 (95% CI of 7.6 to 40.7) in favor of urban residence. Statistically significant (p<0.05) differences is found in term of annual income of family, frequency of physical training sessions conducted in schools, frequency of restaurant & school canteen food. No statistically significant association was found between two categories (higher BMI & normal BMI) with other factors viz. breakfast before school, liking for fast food, involvement in outdoor sports, operating gadgets during meals and having obese family members. Conclusions: Obesity and overweight is more prevalent in urban adolescent. There is no difference among male and female group. There is tendency of high frequency of obesity and overweight among those adolescents who have higher annual family income, frequency of restaurant and school canteen food and lesser frequency of physical training sessions conducted in schools.